In Hannover. Original photo by Atelier Friedrich Wunder, BG A9/340. Writing from Benedikt Kautsky (?) on the back: "Frau Dr. Daniels, von ihrem altem Freunde Karl Marx. London 25 Juni 1870."
In Hannover. Original photo by Atelier Friedrich Wunder, BG A9/340. Writing from Benedikt Kautsky (?) on the back: "Frau Dr. Daniels, von ihrem altem Freunde Karl Marx. London 25 Juni 1870."